The Effect of Whistleblowing Intention on Fraud Prevention with Religiusity as a Moderation Variable - Brian Novan Gilang Ramadhan; Erma Setyowati (International Journal of Economics Development Research (IJEDR), 2023)
This study aims to determine the effect of Whistleblowing Intention on fraud prevention with religiosity as a moderating variable carried out at the Department of Industry and Trade of Magelang City. The method used in this research is a quantitative research method. The number of respondents used in this study were 49 respondents who were taken using the Convinience Sampling technique for employees working at the Department of Industry and Trade of Magelang City. The data source used in this study is primary data collected by distributing questionnaires using Google Forms to prospective respondents. Testing the data used in this study is a descriptive statistical test, validity test, reliability test, classic assumption test and moderating regression analysis (MRA) test, the software used to process the data is SPSS 22. The results of this study indicate that Whistleblowing Intention has a positive effect on fraud prevention. Meanwhile, religiosity has an influence on the relationship between whistleblowing intentions and fraud prevention.